Peritonitis - Warady, Bradley A.; Schaefer, Franz (Pediatric dialysis, 2004)
Peritonitis is the major complication of dialysis in pediatric patients receiving either continuous ambulatory peritoneal dialysis (CAPD) or automated peritoneal dialysis (APD)1,2. The infection can have a significant impact on the long-term outcome of effective dialysis in children who may be dependent upon a functional peritoneum for a prolonged period of time3. In addition, data from the United States Renal Data System (USRDS) has documented that infection, primarily peritonitis, is the most frequent cause for the initial hospitalization of children on PD, while the North American Pediatric Renal Transplant Cooperative Study (NAPRTCS) registry has revealed that peritonitis is the primary reason for modality change in the PD population4,5.